Exploring Hero, Trickster, and Shadow Archetypes in Winnie Holzman’s Wicked - Maharani, Angelia Brigita; Litaay, Adeline Grace M. (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
. This study explores Elphaba's character in Winnie Holzman's Wicked screenwriting by examining her archetypes and her narrative structure through the stages of the Hero's Journey and the archetypal roles of shadow and trickster in shaping her character development. This research uses a descriptive qualitative method with a data collection technique in the form of documentary study. The primary data source in this research is Winnie Holzman's Wicked screenwriting. The results of this research show that the 12 stages of the Hero's Journey formulated by Christopher Vogler as an adaptation of Joseph Campbell are thoroughly identified in the transformation of Elphaba, who is the main character. Other archetypes, such as shadow and trickster, contribute significantly to the conflicts that shape Elphaba's character development. This research provides evidence that myths and classical narrative structures of traditional stories and symbolic archetypes remain relevant for analyzing modern literary works, especially in revealing complex female characters. Through her conflict with the shadow and her interaction with the trickster, Elphaba develops from a recluse to a more confident, independent, courageous defender of justice, and accepting person.